Enabling cytoplasmic delivery and organelle targeting by surface modification of nanocarriers. (July 2015) - Parodi, Alessandro; Corbo, Claudia; Cevenini, Armando; Molinaro, Roberto; Palomba, Roberto; Pandolfi, Laura; Agostini, Marco; Salvatore, Francesco; Tasciotti, Ennio
Nanocarriers are designed to specifically accumulate in diseased tissues. In this context, targeting of intracellular compartments was shown to enhance the efficacy of many drugs and to offer new and more effective therapeutic approaches. This is especially true for therapies based on biologicals that must be encapsulated to favor cell internalization, and to avoid intracellular endosomal sequestration and degradation of the payload. In this review, we discuss specific surface modifications designed to achieve cell cytoplasm delivery and to improve targeting of major organelles; we also discuss the therapeutic applications of these approaches. Last, we describe some integrated strategies designed to sequentially overcome the biological barriers that separate the site of administration from the cell cytoplasm, which is the drug's site of action.